Validity of an Interactive E-Worksheet Based on Guided Inquiry on Environmental Pollution Material to Train Science Process of Grade 10 Senior High School Students - Natasha Alivia; Tarzan Purnomo (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2026)
Science process skills are among the essential competencies that students must master in the 21st century. However, the level of science process skills among students in Indonesia remains relatively low and has not been optimally developed in classroom learning activities. The development of interactive electronic student worksheets (E-LKPD) represents a strategic approach to enhancing student's science process skills. This study aims to develop a guided inquiry-based interactive E-LKPD on environmental pollution to train student's science process skills and to evaluate its feasibility based on its validity. The developed E-LKPD offers several innovative features, including automatic time tracking, integration within a single website without the need to switch between pages, automatic feedback for each question and overall performance, as well as offline accessibility. This study employed the 4D development model (Define, Design, Develop, and Disseminate). The feasibility of the E-LKPD was evaluated by a content expert, an education expert, and a high school biology teacher. The validation process evaluated three dimensions: presentation, content, and language, using a 4-point Likert scale ranging from 1 (poor) to 4 (excellent). The validity data were analyzed statistically by calculating the average score. The results showed that the E-LKPD obtained a presentation validity score of 98.33%, a content validity score of 100%, and a language validity score of 98.33%. With a cumulative score of 98.89%, the E-LKPD was categorized as highly valid. The results indicate that the guided inquiry-based interactive E-LKPD on environmental pollution is suitable for classroom implementation to train student's science process skills.